Digital Marketing and Modern Management to Build Competitive Advantage for Pineapple Fiber MSMEs at Omah Kreatif Indy Prabumulih - Ahmad Maulana; Nurkardina Novalia; Aslamia Rosa; Een Endasari (Penerbit Goodwood, 2026)
Purpose: This community service program aims to strengthen the competitive advantage of pineapple fiber MSMEs, Omah Creative Indy in Prabumulih, through digital marketing strategies and modern management practices to improve production capacity, branding, managerial skills, and business sustainability. Methodology: The program used a qualitative descriptive and participatory approach through field observations, in-depth interviews, and documentation. The implementation was conducted in sequential stages, including socialization, training, technology introduction, mentoring, and evaluation. Data validity was ensured through triangulation, while data were analyzed using reduction, display, and conclusion drawing.Results: The program improved partners’ skills in digital marketing, business management, and product development. The use of new machinery increased production capacity and product quality, enabling more varied and consistent pineapple fiber products. Partners also became more capable of using social media and e-commerce platforms, increasing product visibility and brand positioning.Conclusions: Digital marketing integration, modern management, technology adoption, and continuous mentoring successfully enhanced MSME competitiveness, production efficiency, managerial capability, and digital market reach. Limitations: The program remains limited by product design innovation, capital access, and advanced digital marketing skills. Contributions: This program supports local MSME empowerment and offers a collaboration model between academia, government, and MSMEs in developing creative industries based on natural resources.